A 128 × 128 pixel 120-dB dynamic-range vision-sensor chip for image contrast and orientation extraction. - Ruedi, P.-F (IEEE Journal of solid state circuits)
A vision sensor for low-cost, fast, and robust vision systems is described. The sensor includes an on-chip analog computation of contrast magnitude and direction of image features. A temporal ordering of this information according to the contrast magnitude is used to reduce the amount of data delivered. This sensor, realized in a 0.5-μm two-poly three-metal technology, features a contrast sensitivity of 2%, a contrast direction precision of ±3°, and an illumination dynamic range of 120 dB. Applications with uncontrolled lighting conditions are ideal for this sensor.